2014
DOI: 10.1080/07055900.2014.939131
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Environment Canada's MESH Modelling System over the Great Lakes Basin

Abstract: This paper reports on recent progress towards improved predictions of a land surface-hydrological modelling system, Modélisation Environmentale-Surface et Hydrologie (MESH), via its calibration over the Laurentian Great Lakes Basin. Accordingly, a "global" calibration strategy is utilized in which parameters for all land class types are calibrated simultaneously to a number of sub-basins and then validated in time and space. Model performance was evaluated based on four performance metrics, including the Nash-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 50 publications
(64 reference statements)
1
23
0
Order By: Relevance
“…MESH is a semi‐distributed coupled land surface–hydrology modelling system developed by ECCC for large‐scale watershed modelling with consideration of cold region processes in Canada (Pietroniro et al, ). It has been widely used in different parts of Canada (e.g., Davison et al, ; Haghnegahdar et al, ; Mekonnen et al, ; Mengistu & Spence, ; Pietroniro et al, ; Pohl & Marsh, ) and has been under continuous development at the National Hydrology Research Centre in Saskatoon, Canada, via collaboration between researchers from the GIWS and ECCC.…”
Section: Mesh Modelling Systemmentioning
confidence: 99%
“…MESH is a semi‐distributed coupled land surface–hydrology modelling system developed by ECCC for large‐scale watershed modelling with consideration of cold region processes in Canada (Pietroniro et al, ). It has been widely used in different parts of Canada (e.g., Davison et al, ; Haghnegahdar et al, ; Mekonnen et al, ; Mengistu & Spence, ; Pietroniro et al, ; Pohl & Marsh, ) and has been under continuous development at the National Hydrology Research Centre in Saskatoon, Canada, via collaboration between researchers from the GIWS and ECCC.…”
Section: Mesh Modelling Systemmentioning
confidence: 99%
“…Validation of the previous version of CLASS has been performed as part of Project for Inter-comparison of Land Surface Parameterization (PILPS) [52][53][54]. Langlois et al [55] and Haghnegahdar et al [56], have evaluated the performance of the recent version 3.5 of CLASS, but when coupled with RCMs, focusing on snow simulations and hydrological modelling.…”
Section: Methodsmentioning
confidence: 99%
“…DDS has been successfully applied to a number of case studies before and has shown to be efficient for finding good solutions in complex models with limited calibrated budget (e.g. Dornes et al ., ; Haghnegahdar et al ., ; Tolson and Shoemaker, ). Razavi et al .…”
Section: Case Study: Mesh Model Applied To the Nottawasaga River Basinmentioning
confidence: 97%
“…Modélisation Environmentale–Surface et Hydrologie (MESH) is a land surface‐hydrological model developed by Environment Canada (Pietroniro et al ., ) for various water resources management applications mostly at large scales (e.g. Deacu et al ., ; Dupont et al ., ; Haghnegahdar et al ., ). MESH evolved from WATCLASS (Soulis et al ., ), which was a combination of the routing module of WATFLOOD (Kouwen et al ., ) and the land surface scheme CLASS (Verseghy, ; Verseghy et al ., ).…”
Section: Case Study: Mesh Model Applied To the Nottawasaga River Basinmentioning
confidence: 98%
See 1 more Smart Citation